Totalitarian Opportunism : Cataclysm, Nietzschean Thought and Cultural Transformation in J. J. Conningtons Nordenholts Million (1923) - Jennifer, Woodward (Journal for Religion, Film and Media, 2019)
This article considers J. J. Connington’s 1923 British disaster novel Nordenholt’s Million as a response to its British inter-war context by examining the novel’s presentation of cataclysm as an opportunity for social change. Nordenholt’s Million utilises an apocalyptic scenario involving soil denitrification as a means of offering an uncompromising critique of conventional government systems and its wider social context. Drawing upon the appeal of extreme politics and displaying affinities with Nietzschean philosophy throughout, Nordenholt’s Million emphasises the necessity of dictatorship during periods of social and economic difficulty. It uses such circumstances to champion social transformation from what it presents as a state of contemporary decline towards a highly efficient, eugenically constructed post-apocalyptic utopian society.